PELAKSANAAN PROGRAM KELUARGA HARAPAN (PKH) DALAM MENGENTASKAN KEMISKINAN DI GAMPONG SUAK RAYA KECAMATAN JOHAN PAHLAWAN - Asmaul Husna; Arfriani Maifizar (Jurnal Society : Pengamat Perubahan Sosial, 2023)
Program Keluarga Harapan was a program planned by the government of Indonesia in 2007, the main objective of the Program Keluarga Harapan (PKH) ini Gampong Suak Raya, Johan Pahlawan sub district was not solely to reduce poverty, but also to enhancethe overall quality of human resources, with a particular focus on the local population. The PKH program aimed to achieve this by addressing two key factors: improving the quality of education and enhancing the health of the community. Program Keluarga Harapan (PKH) in Gampong Suak Raya, Johan Pahlawan subdistrict, West Aceh regency had run for years, from 2018 to 2022. In the implementation Program Keluarga Harapan (PKH) was hoped to help the financial condition of poor people. This study used a qualitative method, run in Gampong Suak Raya, Johan Pahlawan subdistrict, West Aceh regency. For this study, the research data collection was done throughdocumentation, interview, and also observation. The result of this study showed that the implementation of Program Keluarga Harapan (PKH) can help the family who received the benefit as the effort to fight the poverty in Gampong Suak Raya, Johan Pahlawan subdistrict, West Aceh regency.